Akomodasi Common Law System Dalam KUHP Baru: Konsep Hukuman Kerja Sosial Sebagai Alternatif Pidana - Khaidarulloh, Khaidarulloh (Institut Agama Islam Negeri Ponorogo, 2023)
In the context of modern society, an effective and efficient legal system is of paramount importance. This article delves extensively into the concept of community service orders as an alternative to imprisonment and fines in the new Indonesian Penal Code (KUHP). The objective is to expound upon the significance of this concept and provide recommendations concerning changes in the legal system. A descriptive methodology is employed in this study to explore various perspectives on this issue and offer profound insights into the concept. The findings indicate that community service orders hold the potential to enhance the effectiveness of the penal system and contribute to the goals of rehabilitation and justice in modern society. However, for the successful implementation of this concept, a robust understanding of the practical aspects is necessary, including the choice of locations, clear legal regulations, and learning from the experiences of other countries that have adopted community service orders. These experiences can serve as a source of inspiration to minimize potential obstacles in the implementation of community service orders in Indonesia.